An overview of the full-chain key technical features in offshore geological carbon sequestration - Ying Teng; Yiqi Chen; Pengfei Wang; Senyou An; Cunbao Li; Jinlong Zhu; Songbai Han; Bao Yuan; Ji Kong; Jingsheng Ma; Yusheng Zhao; Jianbo Zhu (Energy Reviews, 2025)
Geological carbon sequestration (GCS) offers a promising approach to mitigating greenhouse gas emissions and supporting global carbon neutrality goals. Offshore GCS, which leverages subsea geological formations, provides advantages over onshore options in terms of storage capacity, public acceptance, and minimized environmental risks to populated regions, making it a socially, economically, and environmentally viable pillar of global Carbon Capture and Storage strategies. This approach involves injecting captured CO2 into subsea formations through wells, where it can be securely trapped via structural, residual, solubility, and mineral mechanisms over geological timescales. Successful deployment requires addressing the full GCS chain, including site selection, subsurface characterization, and engineering aspects such as platform construction, operational reliability, and risk monitoring. Despite its potential and growing attention, key technical challenges remain insufficiently addressed. This study aims to fill this gap by systematically reviewing essential geoscience and engineering elements of offshore GCS. It examines site selection, trapping efficiency, and operational issues, and provides a detailed evaluation of current and planned offshore GCS projects, with a tabulated dataset to support reference and comparison. The findings highlight research priorities and support the advancement of offshore GCS technologies toward safe and effective implementation.